2013
DOI: 10.1002/ldr.2258
|View full text |Cite
|
Sign up to set email alerts
|

At What Depth Are The Properties of a Gypseous Forest Topsoil Affected By Burning?

Abstract: Wildfires represent one of the main factors of land degradation in Mediterranean environments having negative effects to several ecosystem services. In this work, the fire‐induced changes associated with depth (O horizon and Ah at 0–1, 1–2 and 2–3 cm depths) were studied in a gypseous soil under Aleppo pine forest. Topsoil monoliths were burned in an outdoor combustion tunnel simulating a fire of moderate intensity. In the O horizon, burning caused an immediate and significant decrease in water repellency (WR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…The direct and indirect effects of fire were often studied in soil surface (e.g., Arocena and Opio, 2003;Huseyin, 2006;Thomaz and Fachin, 2014;Meira-Castro et al, 2015;Armas-Herrera et al, 2016;Aznar et al, 2016), but some works showed that these effects reach deeper soil layers, at least down to 30 cm (Fonseca et al, 2011;Dennis et al, 2013;Heydari et al, 2017). The present work is in agreement with the results presented by the former authors, contributing to reinforce the idea that more attention should be given to the direct and indirect effects of fire at deeper depths.…”
Section: Depthsupporting
confidence: 91%
“…The direct and indirect effects of fire were often studied in soil surface (e.g., Arocena and Opio, 2003;Huseyin, 2006;Thomaz and Fachin, 2014;Meira-Castro et al, 2015;Armas-Herrera et al, 2016;Aznar et al, 2016), but some works showed that these effects reach deeper soil layers, at least down to 30 cm (Fonseca et al, 2011;Dennis et al, 2013;Heydari et al, 2017). The present work is in agreement with the results presented by the former authors, contributing to reinforce the idea that more attention should be given to the direct and indirect effects of fire at deeper depths.…”
Section: Depthsupporting
confidence: 91%
“…Fire may alter physicochemical soil properties (i.e., soil organic matter content and structure, hydrophobicity, pH and nutrient cycles) and microbiological or biochemical soil properties (i.e., microbial biomass, microbial activity, soil enzymes activities) (Mataix-Solera et al, 2009). These changes mostly occur below 5 cm of the surface, where the soil temperature rarely overtakes 100 • C (Úbeda and Outeiro, 2009;Aznar et al, 2013). Post-fire silvicultural treatments may also modify the soil microbiological and biochemical variables, such as belowground biological activity and soil nutrients' availability (Grady and Hart, 2006) or enzyme activities (Wic-Baena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of fire on SOM quality continue an important research gap, also because recent advances and, in particular, the use of pyrolysis gas chromatography/mass spectrometry (Py-GC/MS), also called analytical pyrolysis, have shown that these effects can be very complex (Aznar et al, 2013;Badía-Villas et al, 2014a;De la Rosa et al, 2008bGonzález-Pérez et al, 2004). Analytical pyrolysis provides information concerning the structure of organic molecules, including N species, which cannot be released by hydrolysis.…”
Section: Introductionmentioning
confidence: 99%